Income Inequality and Self-Reported Values - Giacomo Corneo; Frank Neher (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper offers a comprehensive econometric investigation of the impact of income inequality on the values endorsed by people. Using survey data from all thirty-four OECD countries over a period of almost thirty years, the following dimensions of value systems are investigated: work ethic, civism, obedience, honesty, altruism, and tolerance. In most cases, no robust effects from inequality on values are detected. However, there is evidence that a more unequal income distribution strengthens the work ethic of the population. Thus, income inequality seems to generate work incentives not only via the pecuniary reward of work but also through the symbolic reward it receives.
urn:nbn:de:bvb:19-epub-13172-4
Keywords: D63; O15; O57; Z1; 330; Income inequality; Value systems; Einkommensverteilung; Soziale Werte; Schätzung; OECD-Staaten